Comparative geographical analysis of the level of socio-economic development of the regions in European Russia - Natalia Aleksandrovna Shchitova; Vasily Vasil'yevich Chihichin (Наука. Инновации. Технологии, 2022)
In this paper an example of Smolensk region, Belgorod region and Stav-ropol region is shown heterogeneity of socio-economic development of the regions of European Russia. Marked general and specific problem areas of socio-economic processes, the degree of influence of a factor.